Examining Atmospheric River Life Cycles in East Antarctica - Wille, Jonathan D.; Pohl, Benjamin; Favier, Vincent; Winters, Andrew C.; Baiman, Rebecca; Cavallo, Steven M.; Leroy-Dos Santos, Christophe; Clem, Kyle; Udy, Danielle G.; Vance, Tessa R.; Gorodetskaya, Irina; Codron, Francis; et al. (Wiley, 2024)
During atmospheric river (AR) landfalls on the Antarctic ice sheet, the high waviness of the circumpolar polar jet stream allows for subtropical air masses to be advected toward the Antarctic coastline. These rare but high-impact AR events are highly consequential for the Antarctic mass balance; yet little is known about the various atmospheric dynamical components determining their life cycle. By using an AR detection algorithm to retrieve AR landfalls at Dumont d'Urville and non-AR analogs based on 700 hPa geopotential height, we examined what makes AR landfalls unique and studied the complete life cycle of ARs reaching Dumont d'Urville. ARs form in the mid-latitudes/subtropics in areas of high surface evaporation, likely in response to tropical deep convection anomalies. These convection anomalies likely lead to Rossby wave trains that help amplify the upper-tropospheric flow pattern. As the AR approaches Antarctica, condensation of isentropically lifted moisture causes latent heat release that-in conjunction with poleward warm air advection-induces geopotential height rises and anticyclonic upper-level potential vorticity tendencies downstream. As evidenced by a blocking index, these tendencies lead to enhanced ridging/blocking that persist beyond the AR landfall time, sustaining warm air advection onto the ice sheet. Finally, we demonstrate a connection between tropopause polar vortices and mid-latitude cyclogenesis in an AR case study. Overall, the non-AR analogs reveal that the amplified jet pattern observed during AR landfalls is a result of enhanced poleward moisture transport and associated diabatic heating which is likely impossible to replicate without strong moisture transport. ISSN:0148-0227 ISSN:2169-897X